Pemodelan Konsep Augmented Reality Motif Batik Dayak Kalimantan Timur - Andi Tejawati; Joan Angelina Widians; Renol Sulle; Muhammad Bambang Firdaus; Anton Prafanto; Faza Alameka (LPPM Universitas Mulia, 2022)
Indonesian Batik has been designated as a Humanitarian Heritage for Oral and Intangible Culture by UNESCO since October 2, 2009. Although Batik is well known to the Indonesian people, many people are unfamiliar with batik motifs from the region. One of them is the East Kalimantan Dayak Batik motif. The introduction of information media has followed the development of existing technology. One of them is the introduction of media by utilizing AR technology. Augmented Reality (AR) is a technology that allows computers to display virtual objects precisely on natural objects in real-time. Introducing the East Kalimantan Dayak Batik Motif using Augmented Reality technology is expected to be a more interactive alternative for introducing Indonesian culture, especially in East Kalimantan. The results show that the Augmented Reality (AR) application for the East Kalimantan Dayak Batik motif has been successfully designed and built using the Vuforia SDK, Blender, and Unity3D software. Testing Distance, occlusion, and light intensity are very influential in detecting markers.